Pilot study: knowledge and awareness regarding asthma among publics of Hospital Taiping, Perak - Fakruzaman, Nurlisa Hanim; Yusof, Nurul Asyikin (2017)
Knowledge and awareness towards asthma among publics in out-patients department of Hospital Taiping has been explored. This study focuses on level of education towards good knowledge and awareness of asthma among publics. Our study was done at Hospital Taiping, Perak which is visited from almost patients and caregivers from Perak because this hospital has many experts in their medical filled. This study seems to be important to obtain a statistic from the survey done to the population. Our study subject was the publics who come to the outpatient pharmacy department of Hospital Taiping, Perak on February 2017 which represent the publics out there. They were chosen conveniently and then we gave a set of questionnaire for them to answer. The focus of this study is to relate their demographic factors which are ages, gender, level of education, and experiences on asthma themselves to the knowledge and awareness questionnaire on the different part on the questionnaire. From the 260 filled questionnaires we manage to collect, we go through all of it and key in the data into Statistical Package of Social Sciences (SPSS) version 23.0 software to get the result in table form and also graph form. Expectedly, all the respondent are aware 274(1000/o) of asthma disease and roughly they have the interest to know about it better. Instead, this result will be fully used soon on how to improve public awareness and knowledge asthma. Thus, the government might achieve their real objectives of conducting this programme.